Chapter Rivivere la storia tra scuola e territorio. Due esperienze di re-enactment e living history in Toscana - Bravi, Luca (Public History of Education. Teorie, esperienze, strumenti, 2022)
The essay describes how Living History, an activity of concrete evocation of past events in the present, linked to the daily actions of the historical period described, is intertwined with the approach of "material civilization" developed by Fernand Braudel and with micro-history described by Lucien Febvre and March Bloch in connection with the Annales methodology. The re-enactment, if it is built according to correct theoretical and methodological references, linked to historical documents, devoid of folklore, can represent a useful tool for building popular participation and knowledge about events and characters from the past.